KEABSAHAN PENGGUNAAN KUASA MUTLAK DALAM PERJANJIAN PENGIKATAN JUAL BELI (PPJB) TANAH YANG DIBUAT OLEH NOTARIS - Clara Vania; Gunawan Djajaputra (Jurnal Hukum Adigama, 2018)
Absolute power of attorney is a power of attorney containing an irrevocable element by the authorizing party. Since the Instructions of the Minister of Home Affairs Number 14 Year 1982 concerning the Prohibition of Absolute Power of Attorney as the Transfer of Land Rights took effect on 6 March 1982 and Government Regulation Number 24 Year 1997 concerning Land Registration took effect on 8 July 1997, the use of absolute power of attorney has been banned. But in the practice, the use of absolute power of attorney in the Binding Sale and Purchase Agreement of Land is still found. This is what often causes conflict because the use of absolute power of attorney is considered contrary to the laws and regulations in Indonesia. The formulation of the problem in this thesis is how the validity of the use of absolute power of attorney in the Binding Sale and Purchase Agreement of Land made by a public notary and how the legal consequences of the Binding Sale and Purchase Agreement of Land that use absolute power of attorney. The results of the study showed that regarding the use of absolute power of attorney in the Binding Sale and Purchase Agreement of Land is legal and does not violate the laws and regulations. In addition, the legal consequences arising from the use of this absolute power of attorney in the Binding Sale and Purchase Agreement of Land are still recognized and remain valid and binding for the parties who have made them.